2019
DOI: 10.1109/access.2019.2944028
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Models of Breakdown Voltage and Specific On-Resistance for Vertical GaN Unipolar Devices

Abstract: In this paper, the analytical models of breakdown voltage design parameters and minimum specific on-resistance in vertical gallium nitride unipolar devices are proposed. Considering the discrepancy of the impact ionization coefficients (IIC) reported in previous literatures from the Monte Carlo simulations and experiments, the analytical models of avalanche breakdown of gallium nitride devices both in punchthrough and non-punch-through conditions are presented, i.e., the relationship between the breakdown volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…The model for the low-field mobility 30) in the drift region is given by Specifically, with a m CH of 60 cm 2 /V•s, the calculated R on sp , is 2.1 mΩ•cm 2 and 2.5 mΩ•cm 2 for the T-MOSFETs and SR-MOSFETs, respectively, which agrees well with the simulation results in Fig. 8(b).…”
Section: Effect Of the P-sr Thickness On The Electrical Properties Of...supporting
confidence: 83%
“…The model for the low-field mobility 30) in the drift region is given by Specifically, with a m CH of 60 cm 2 /V•s, the calculated R on sp , is 2.1 mΩ•cm 2 and 2.5 mΩ•cm 2 for the T-MOSFETs and SR-MOSFETs, respectively, which agrees well with the simulation results in Fig. 8(b).…”
Section: Effect Of the P-sr Thickness On The Electrical Properties Of...supporting
confidence: 83%
“…A few groups recently reported that the "GaN limit" calculated based on the impact ionization coefficients is very similar to the present SiC limit. 52,53) In Fig. 4, the R on -V B characteristics of reported SiC power MOSFETs are plotted as red closed circles.…”
Section: ( )mentioning
confidence: 99%